Anti transglutaminase antibodies cause ataxia in mice. - Sabrina Boscolo; Andrea Lorenzon; Daniele Sblattero; Fiorella Florian; Marco Stebel; Roberto Marzari; Tarcisio Not; Daniel Aeschlimann; Alessandro Ventura; Marios Hadjivassiliou; Enrico Tongiorgi (PLoS ONE)
Background Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. Methods We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. Conclusion The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.